Deskripsi Kemampuan Psikomotor Melalui Model Pembelajaran Kooperatif Berbasis Simulasi Phet Dan Alat Praktikum Seserhana - suci ningtyas (Universitas KH. A. Wahab Hasbullah, 2019)
This study aims to describe psychomotor ability and student response to learning through cooperative learning model by using PhET simulation Circuit Construction kit and simple practicum tool on the subject of direct current circuit. The method used in this research is descriptive method. The subject of this research is Physics Education 2nd semester of Faculty of Education Science Universitas KH. A. Wahab Hasbullah. Measurement of learning outcomes psychomotor domain using performance tests or action tests. The method used in this research is descriptive method. Measurement of learning outcomes psychomotor domain using performance tests or action tests. Technique data collection used in this research is a technique observation with data sheets of observation skill psychomotor and response students to learning. Based on the results of research and discussion can be concluded that the psychomotor ability of students who taught using simple practicum tools is better than PhET simulation. It appears that students taught using PhET simulations and simple practicum tools (APS) for the average moving aspect (80-89%) are categorized very well. The communicating aspect is categorized as excellent (81-85%) for the use of APS while for PhET simulation is good (75-80%). The aspect of creating overall is a good category with an average score (76-80%). Whereas student's response to learning using simple practice simulation tool categorized well with the average percentage of 82% for learning using simple practicum tools compared with using PhET simulation (good category with the average percentage of 81%).